2008
DOI: 10.1597/06-151.1
|View full text |Cite
|
Sign up to set email alerts
|

Folate and Clefts of the Lip and Palate—A U.K.-Based Case-Control Study: Part II: Biochemical and Genetic Analysis

Abstract: While the inverse relation between the mother's having the MTHFR C677T variant and both CL+/-P and CP suggests perturbation of maternal folate metabolism is of etiological importance, contrasting relations between maternal postpartum levels of RBC and serum folate by type of cleft are difficult to explain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 50 publications
(72 reference statements)
0
19
0
4
Order By: Relevance
“…The incidence of clefting in KS patients is significant, as the incidence of cleft lip AE palate in the general population is only 0.1-0.2% [Little et al, 2008]. In addition to cleft lip AE palate, cleft palate alone [Sato et al, 2004] and dental agenesis [Sato et al, 2004] have also been reported in several patients with KS.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of clefting in KS patients is significant, as the incidence of cleft lip AE palate in the general population is only 0.1-0.2% [Little et al, 2008]. In addition to cleft lip AE palate, cleft palate alone [Sato et al, 2004] and dental agenesis [Sato et al, 2004] have also been reported in several patients with KS.…”
Section: Discussionmentioning
confidence: 99%
“…Casecontrol studies of folic-acid containing multivitamin supplements [63][64][65][66][67][68] maternal dietary folate intake [64,67,[69][70][71] and red cell and plasma folate [72][73][74][75] are inconsistent. There is some evidence that periconceptional multivitamin supplementation can reduce the birth prevalence of orofacial clefts by 30-50% [64,76,77].…”
Section: Food Fortification With Folic Acid and Multivitaminsmentioning
confidence: 99%
“…In a subsequent Netherlands study, case mothers with low vitamin B 12 and B 6 levels had an increased risk of clefts in their children, whereas folate concentrations were not significantly different between case and control mothers (van Rooij et al, 2003). In a U.K.-based case-control study, higher serum and erythrocyte folate concentrations were associated with decreased risk of CLP but an increased risk of CP (Little et al, 2008b). In the Philippines, low plasma PLP concentrations were common and associated with increased cleft risk, although plasma and erythrocyte folate concentrations were inconsistently associated with cleft risk.…”
Section: Introductionmentioning
confidence: 99%